REKONSTRUKSI IDENTITAS ETNIK: SEJARAH SOSIAL POLITIK ORANG PAKPAK DI SUMATERA UTARA 1958 - 2003 - Agustono, Budi (Masyarakat Indonesia, 2011)
This dissertation aims to analyze the history of the Pakpak people who have been marginalized politically, economically and culturally in the midst of Toba Batak domination since their settlement in Pakpak between the early 20th to early 21st centuries. The result of the research indicates that power may not only defne and revitalize identity, but it is also capable of constructing identity. The reconstruction of ethnic identity may occur because in addition to the existing defnition of ethnicity, customary laws and tradition, there is an opportunity for the Pakpak elite to use their power to manipulate ethnic sentiment.